Unfolding graphene nanosheets towards high barrier performance of epoxy/graphene nanocomposite coating. (February 2022) - Wu, Tingting; Yang, Yanjia; Sun, Wen; Yang, Zhengqing; Wang, Lida; Wang, Jing; Liu, Guichang
Abstract: The improvement of barrier properties brought by graphene is severely restricted for graphene/polymer nanocomposites due to inevitable crumpling and folding of embedded graphene. Herein, graphene was sandwiched into mesoporous silica via a soft-template method, achieving unfolded graphene/SiO2 nanosheets (rGOSs). The barrier properties of the rGOSs-reinforced coatings (rGOSc) are evaluated. Experimental results reveal that, compared with conventional graphene/epoxy coating, the water vapor and oxygen transmission rate of rGOSc decreases by 65.2% and 62.3%, respectively, and corresponding corrosion resistance increases by ∼3–4 orders of magnitude. Numerical results further demonstrate that, comparing with conventional graphene with irregular crumpling and folding morphology, unfolded rGOSs perform better in prolonging and twisting the diffusion pathway of diffusing species in coating matrix.